Análise de confiabilidade, mantenabilidade e disponibilidade de uma mesa de resfriamento de tiras de aço - Santos, Joannerson Dettmann dos (2019)
The main subject of this research a study of reliability, maintainability and availability applied to a hot strip mill roller table. With RAM analysis, it is possible to safely determine the mathematical models involved in order to apply reliability engineering to companies' decision making in any given sequence. Thus, it becomes more assertive to prepare annual budgets based on equipment failure expectations, establishing the component exchange flow ensuring their performance.